Surprise for graduating son, Rahmat entertains guests - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 5 November 2022 - Famous rock singer of the 90s, Rahmad Tohak or Rahmad Mega surprised not only his son but also the guests when performing on stage in conjunction with the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony in the UMP Sports Complex Hall.